1994
DOI: 10.1159/000236712
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bovine Respiratory Syncytial Virus Infection on Hypersensitivity to Inhaled <i>Micropolyspora faeni</i>

Abstract: Respiratory syncytial virus causes mild-to-severe respiratory disease in human infants and young children; a closely related bovine respiratory syncytial virus causes a similar disease pattern in calves. Increased disease severity in atopic children suggests that allergic reactivity may enhance the severity of RSV-induced disease. To examine the association between bovine respiratory syncytial virus (BRSV) infection and allergic reactivity two groups of calves were exposed to aerosolized Micropolyspora faeni (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1997
1997
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…These studies and additional data from a rat model of influenza infection [28] and bovine model of RSV infection [29] demonstrate that viral lower respiratory tract infections can enhance allergic sensitization to inhaled antigens and prevent the development of tolerance which may be induced by allergen exposure via the airways in the absence of infection (table 1). Among the mechanisms involved, increased permeability of the airway mucosa to allergens and recruitment of dendritic cells to the airway epithelium during acute infection may be important, facilitating sensitization through increased antigen uptake and more effective antigen presentation.…”
Section: Parainfluenza Infection Results In Increased Mucosal Permeabmentioning
confidence: 93%
“…These studies and additional data from a rat model of influenza infection [28] and bovine model of RSV infection [29] demonstrate that viral lower respiratory tract infections can enhance allergic sensitization to inhaled antigens and prevent the development of tolerance which may be induced by allergen exposure via the airways in the absence of infection (table 1). Among the mechanisms involved, increased permeability of the airway mucosa to allergens and recruitment of dendritic cells to the airway epithelium during acute infection may be important, facilitating sensitization through increased antigen uptake and more effective antigen presentation.…”
Section: Parainfluenza Infection Results In Increased Mucosal Permeabmentioning
confidence: 93%
“…A conflicting study in a similar guinea pig model showed impaired airway sensitization after parainfluenza type III infection and the loss of airway hyperresponsiveness (30). In a bovine model, RSV infection enhanced sensitization to an inhaled antigen (31).…”
Section: Discussionmentioning
confidence: 99%
“…RSV-infected murine lungs were characterized by increased eosinophilia, cytokine production (including IL-4), and inflammation, including up-regulation of adhesion molecules and chemokines. Additionally, in a bovine model RSV infection has been shown to enhance sensitization to subsequent airway Ag (61,62). Although still controversial, a variety of studies suggest that individuals who suffered an RSV infection during childhood are significantly predisposed to develop allergy and atopy either during early adulthood or later (63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%